2020
DOI: 10.1101/2020.07.31.231779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody:CD47 ratio regulates macrophage phagocytosis through competitive receptor phosphorylation

Abstract: Cancer immunotherapies often modulate macrophage effector function by introducing either targeting antibodies that activate Fc gamma receptors or blocking antibodies that disrupt inhibitory SIRPα-CD47 engagement. Yet how these competing signals are integrated is poorly understood mechanistically, raising questions about how to effectively titrate immune responses. Here we find that macrophage phagocytic decisions are regulated by the ratio of activating ligand to inhibitory ligand on targets over a broad range… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, a shortcoming of this system is that the presented ligands are immobile. In the case of IgSF co‐signalling receptors, it has been demonstrated that co‐clustering between receptors is important because cytoplasmic enzymes bound to one receptor modify another (Dushek et al , 2012; Hui et al , 2017; Suter et al , 2021). Although mobility is important for this receptor‐proximal signal integration (Dushek et al , 2012), it is less clear whether it is important for co‐signalling by TNFRSF members that integrate their signals more distally (Watts, 2005; Zapata et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, a shortcoming of this system is that the presented ligands are immobile. In the case of IgSF co‐signalling receptors, it has been demonstrated that co‐clustering between receptors is important because cytoplasmic enzymes bound to one receptor modify another (Dushek et al , 2012; Hui et al , 2017; Suter et al , 2021). Although mobility is important for this receptor‐proximal signal integration (Dushek et al , 2012), it is less clear whether it is important for co‐signalling by TNFRSF members that integrate their signals more distally (Watts, 2005; Zapata et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Chung et al found that trastuzumab and pertuzumab attenuate tubule structures enriched in HER2, suggesting that biophysical interactions like crowding may influence the potency of mAb therapies (84). Our crowding measurements may also help inform the biophysical mechanisms governing antibody-dependent phagocytosis, which have been recently shown to have a strong dependence on the relative heights of the macrophage Fc γ receptor and the target cell surface proteins (13, 85). In conclusion, our sensors may be used to inform important physiological processes, like antibody binding to buried surface receptors, membrane organization of lipid raft-like domains, and cellular phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages mediate ADCP by recognizing and destroying antibody-opsonized cells in cancer therapy (44). As CD47/SIRPα engagement disrupts ADCP (45) and SHP2 serves as a signal molecular downstream of SIRPα, we wanted to investigate how SHP2 regulated the CD47 checkpoint. Therefore, reconstituted targets imitating antibody opsonized tumor cells were used (Figure 5A), and macrophage-specific Shp2 mφ-/mice were generated (Supplemental Figure 5A).…”
Section: Shp2 Inactivates Integrin αMβ2 To Suppress Phagocytosis Via ...mentioning
confidence: 99%